The Risks and Rewards of Resource-for-Infrastructure Deals: Lessons from the Congo's Sicomines Agreement - David G. Landry (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2018)
This paper by David G. Landry explores the Sicomines agreement and highlights the role risk has played from its inception a decade ago until now. This case reveals how, while simple on the surface, Resource-for-Infrastructure (RFI) deals carry significant risks for their signatories because of the long time horizon through which they operate. This has led the Sicomines agreement to experience many hurdles, both on the infrastructure delivery and resource extraction fronts. Landry employs financial modeling techniques to highlight the pitfalls of attempting to identify a "winner" in such ventures until they reach their conclusion. As demonstrated through the Sicomines case, the expected benefits of RFI deals can change swiftly and unpredictably.
Keywords: 330